2009
DOI: 10.1629/22s1
|View full text |Cite
|
Sign up to set email alerts
|

E-books and user assumptions

Abstract: S1 E-books and user assumptions E-books, in all their forms, are now a core element of library collections, but even as they become a larger part of the publishing world and library holdings, users face new realities that they did not expect. Many are unable to deal with e-books in the way creators envision.There are issues of many kinds related to technology, readability, access, borrowing, and the level of knowledge about special features. Undergirding these is a subtle issue that is becoming more obvious as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…When inquiring about students' awareness of e-books, this study found that nearly a third of respondents were not sure what an e-book was (Primary Research Group, 2009). In reviewing this study and other studies, Soules (2009) remarks:…”
Section: Study At the University Of Illinois Urbana-champagne Also Mamentioning
confidence: 90%
“…When inquiring about students' awareness of e-books, this study found that nearly a third of respondents were not sure what an e-book was (Primary Research Group, 2009). In reviewing this study and other studies, Soules (2009) remarks:…”
Section: Study At the University Of Illinois Urbana-champagne Also Mamentioning
confidence: 90%
“…It is similar to a molting snake. E-books have not yet cast off their print skins, and this colors many issues" (Soules, 2009). …”
Section: E-books and Print Booksmentioning
confidence: 99%
“…In an article, Mikki & Stangeland 12 describes how users find e-books challenging to read because of their user interfaces, restrictions imposed on users to use and specific reading devices required due to proprietary file formats. Similarly, Soule 13 highlighted issues related to technology, readability, access, borrowing, and the level of knowledge that hindering the use of e-books. She believes that there is a need to redefine the concept of e-book.…”
Section: Review Of Related Studiesmentioning
confidence: 99%